2019
DOI: 10.3389/fpsyg.2019.00630
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Meditation Practice: Exploring Their Explanatory Power on Psychological Adjustment

Abstract: There has been increased interest in the relationships between religiosity, meditation practice and well-being, but there is lack of understanding as to how specific religious components and distinct meditation practices could influence different positive and negative psychological adjustment outcomes. The aim of this study was to assess the explanatory power of religious beliefs and the practice of prayer, focused attention (FA), open monitoring (OM), and compassion meditation (CM) on psychological adjustment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 102 publications
(145 reference statements)
0
10
0
Order By: Relevance
“…Avina, 2008 ) and may be beneficial to incorporate into meditation-based interventions. Specifically, self-regulatory behaviours do appear to be important, as lack of skills in goal setting and habit formation appear to interfere with adopting a consistent mindfulness practice (Mrazek et al, 2020 ). In addition, one meta-analysis supports the notion that smartphone apps, text messages, and other online programs may be beneficial in encouraging home practice and recording the frequency of meditation practice (Parsons, Crane, Parsons, Fjorback, & Kuyken, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Avina, 2008 ) and may be beneficial to incorporate into meditation-based interventions. Specifically, self-regulatory behaviours do appear to be important, as lack of skills in goal setting and habit formation appear to interfere with adopting a consistent mindfulness practice (Mrazek et al, 2020 ). In addition, one meta-analysis supports the notion that smartphone apps, text messages, and other online programs may be beneficial in encouraging home practice and recording the frequency of meditation practice (Parsons, Crane, Parsons, Fjorback, & Kuyken, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual fitness is also a way to develop personalized, patient-centered healthcare that may include or transcend religion and accents the process of self-discovery [ 92 ]. KK and spiritual fitness are associated with distinct positive psychological outcomes, many of which can affect cognition, and are more relevant, according to work by Montero-Marin, than even religious beliefs [ 140 ].…”
Section: Spiritual Fitness and Ad Preventionmentioning
confidence: 99%
“…Particularly, seeking and connecting with others for patients with chronically ill plays a role in the promotion of health and healing Lindsey [20]. Montero-Marin & Perez-Yus [24] suggested that nurturing the mind through meditation practices of unifying body and mind, related a positive psychological adjustment. Chan and Ho [25] worked with Chinese cancer patients and witnessed their growth and resilience.…”
Section: Confucius Philosophy Helped To Reconstruct Good Life With Diseasesmentioning
confidence: 99%